Influência da excentricidade e proporção de massa no processo de fusão de PCM em trocadores de calor de múltiplos anéis - Picoli, Franco (Universidade do Vale do Rio dos Sinos, 2021)
Thermal energy storages are an important system for energy storage, having a wide range of use within engineering. Among the existing types, the latent heat ones offer advantages over the others, however, they still have limitations for their application, one of the main ones being the low thermal conductivity of the materials used for energy storage. In this study, the influence of the combination of different geometries, eccentricities and mass proportion between rings on the phase change material (PCM) fusion process in a multi-ring thermal energy store is investigated. The study was carried out by computational fluid dynamics considering a two-dimensional domain. The analyzed PCM was the RT82. For all the analyzed arrangements, the thermal exchange area and the system's PCM mass were kept constant. The numerical model used is composed by the equations of momentum, mass and energy conservation, plus the phase change model. Numerical validation was performed using experimental results taken from the literature. The results of the study reveal that the horizontal square section geometry provided the shortest melting times of the PCM comparing mass proportion between rings and equivalent eccentricities. The increase in the mass ratio between the rings containing PCM contributed to the reduction of the total fusion time in the system, mainly caused by the reduction in the amount of mass in the outer ring, consequently increasing the fusion rate in it. The eccentricity of the tubes contributed to reduce the total melting time, distributing the mass from the lower region to the upper region of the rings where the highest melting rates occur, however there is a limitation, since high eccentricity values excessively increase the amount of mass in the upper region reducing the melt rate. The combination between the increase in the ratio of mass ratio between the rings and the eccentricity helped to reduce the melting time of the PCM, and the optimal combination was the arrangement with horizontal square geometry, 𝜓 = 26/74 %/% and 𝜃 = 10 mm, obtaining a total time of 54.5 min.
Keywords: Armazenadores térmicos; Materiais de mudança de fase; Redução do tempo de fusão; Múltiplos anéis; Proporção de massa; Excentricidade; Thermal energy storages; Phase change materials; Melting time reduction; Multiple rings; Mass proportion; Eccentricity; ACCNPQ::Engenharias::Engenharia Mecânica